2013
DOI: 10.1371/journal.pone.0063561
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Bone Marrow Mesenchymal Stem Cells Caused by Homocysteine via Activating JNK Signal

Abstract: Bone marrow mesenchymal stem cells (BMSCs) are capable of homing to and repair damaged myocardial tissues. Apoptosis of BMSCs in response to various pathological stimuli leads to the attenuation of healing ability of BMSCs. Plenty of evidence has shown that elevated homocysteine level is a novel independent risk factor of cardiovascular diseases. The present study was aimed to investigate whether homocysteine may induce apoptosis of BMSCs and its underlying mechanisms. Here we uncovered that homocysteine signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 41 publications
0
28
0
1
Order By: Relevance
“…Several recent reports have suggested that MAPKs such as ERK1/2 and JNK MAPK exert their roles in response to various apoptotic stimuli (19,20). Figure 2E shows that quercetin promoted pronounced ERK1/2 and JNK phosphorylation in a dose-dependent manner after 24-hour treatment.…”
Section: Resultsmentioning
confidence: 79%
“…Several recent reports have suggested that MAPKs such as ERK1/2 and JNK MAPK exert their roles in response to various apoptotic stimuli (19,20). Figure 2E shows that quercetin promoted pronounced ERK1/2 and JNK phosphorylation in a dose-dependent manner after 24-hour treatment.…”
Section: Resultsmentioning
confidence: 79%
“…BMSCs apoptosis was detected using acridine orange/ethidium bromide (AO/EB) staining [19]. The cultured BMSCs were treated with different concentrations of doxorubicin for 48 h. In order to label the apoptotic cells, 10 μL prepared AO/EB working solution (100 μg/mL AO and 100 μg/mL EB in PBS) was added to the cells for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Effects of doxorubicin on BMSCs apoptosis were determined using Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay as described previously [19]. The cultured BMSCs were fixed with 4% paraformaldehyde for 1 h at room temperature, blocked and then permeabilized in 0.1% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that ROS production regulates aging, senescence, and osteogenic differentiation in mesenchymal stem cells [23,24]. To further evaluate the effects of blue LED irradiation on ROS production, we performed DCF-DA staining in blue LED treated and untreated BMSCs.…”
Section: Increased Intracellular Reactive Oxygen Species (Ros) Levelsmentioning
confidence: 99%